Cortical Recruitment and Nuclear–Cytoplasmic Shuttling of Scd5p, a Protein Phosphatase-1-targeting Protein Involved in Actin Organization and Endocytosis - Chang, Ji Suk (The American Society for Cell Biology, 2006)
Scd5p regulates endocytosis and cortical actin organization as a targeting subunit for the Ser/Thr protein phosphatase-1 (PP1) in yeast. To identify localization signals in Scd5p required for cell surface recruitment, visualization of GFP-tagged Scd5 truncations and deletions was performed. Scd5p contains a PP1 binding site, a 3-repeat region of 20 amino acids (3R), and a 9-repeat region of 12 amino acids (9R). We found that the 9R is critical for cortical localization of Scd5p, but cortical recruitment is not essential for Scd5p's function in actin organization and endocytosis. We propose that Scd5p can target PP1 to endocytic factors in the cytoplasm that have been disassembled and/or inactivated by phosphorylation. We also found that Scd5p undergoes nuclear-cytoplasmic shuttling in a Crm1p-dependent manner. Scd5p-ΔCT lacking the 9R region and its nuclear export signal (NES) accumulates in the nucleus, causing cortical actin and endocytic defects. Cytoplasmic localization and function of Scd5p-ΔCT is restored by NES addition. However, removal of Scd5p's nuclear localization signal prevents nuclear entry, but endocytosis and actin organization remain relatively normal. These results indicate that nuclear-cytoplasmic shuttling is not required for regulation of Scd5p's cortical function and suggest that Scd5p has an independent nuclear function.